2012
DOI: 10.1136/tobaccocontrol-2011-050249
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the health impacts of smoking and public attitudes towards tobacco control in the former Soviet Union

Abstract: Aim To describe levels of knowledge on the harmful effects of tobacco and public support for tobacco control measures in nine countries of the former Soviet Union, and to examine the characteristics associated with this knowledge and support. Methods Standardised cross-sectional, nationally representative surveys conducted in 2010/11 with 18000 men and women aged 18 years and above in Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia, and Ukraine. Respondents were asked a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Smoking prevalence appears to have stabilized and may be declining in younger groups, but remains extremely high among men, especially those in lower socioeconomic groups. Large gaps exist in public understanding of the negative health effects of tobacco use, particularly in Kazakhstan (Roberts et al, 2012a;2012b). The decreases observed in younger males are thus in line with expectation from smoking rates, as is the gender variation.…”
Section: Discussionmentioning
confidence: 56%
“…Smoking prevalence appears to have stabilized and may be declining in younger groups, but remains extremely high among men, especially those in lower socioeconomic groups. Large gaps exist in public understanding of the negative health effects of tobacco use, particularly in Kazakhstan (Roberts et al, 2012a;2012b). The decreases observed in younger males are thus in line with expectation from smoking rates, as is the gender variation.…”
Section: Discussionmentioning
confidence: 56%
“…A survey conducted in nine former Soviet countries during 2010–2011 observed that only 36.8% of adults supported a total ban of smoking in restaurants, bars and cafes in Russia. In the same study, the corresponding figure was 38.2% in Ukraine and 30% in Georgia 55. It is well known that the exact form of question wording in survey research can have a significant influence on findings, and this is sometimes exploited by pollsters who are affiliated with candidates, campaigns and causes.…”
Section: Discussionmentioning
confidence: 89%
“…Life satisfaction and happiness ratings are especially low in Eastern Europe and fSU countries such as Russia,26 27 while tobacco has a large impact on the disease burden in Eastern Europe,28 with smoking-related mortality being especially high in the fSU countries 29. Although there is evidence that the prevalence of smoking has stabilised in the countries in this region in recent years, it nevertheless remains very high among men,30 and understanding of the effects of tobacco use on health is still limited among the general public,31 as manifest, possibly, in low quit ratios 32. On the other hand, there is a high desire to stop smoking among individuals in these countries 32.…”
Section: Introductionmentioning
confidence: 99%